Amelioration of inflammatory responses by Chlorogenic acid via suppression of pro-inflammatory mediators - Prashant Singh Chauhan, Naresh Kumar Satti, Vijay Kumar Sharma, Prabhu Dutt, Krishan Avtar Suri, Sarang Bani (Journal of Applied Pharmaceutical Science)
The premise of the present investigation was to evaluate the detailed anti-inflammatory properties of chlorogenic acid (CGA) and to delineate the possible mode of action. To explore the anti-inflammatory profile, we evaluated the effect of CGA on TNF-alpha expression (in vitro); carrageenan induced rat paw edema and carrageenan induce pleurisy (in vivo). In our studies, CGA significantly inhibited the TNF-alpha expression, paw edema and antioxidant enzymes in livers of rats in pre-treatment schedule but failed to exert any effect when administered 1 h after carrageenan injection. CGA was also found to be safe, as confirmed by the results of acute toxicity studies and MTT assay. CGA also caused reduction in total leucocytes count most probably by inhibiting neutrophils, but could not alter mononuclear cells count in carrageenan induced pleurisy. Inhibition of exudation was evidenced by the less exudate formation in CGA treated animals, which may be due to decrease in vascular permeability which was further confirmed in acetic acid induced vascular permeability model in mice where significant decrease in vascular permeability was observed. CGA was highly effective in reducing the arachidonic acid metabolites, nitric oxide and pro-inflammatory cytokines production in a dose dependent manner and in some conditions effect observed was almost comparable to ibuprofen. Result of the present investigation shows the anti-inflammatory effects of CGS in different models.
Keywords: Chlorogenic acid, pro-inflammatory cytokines, nitric oxide, PGE2, LTB4.